(untitled) (Faridpur Medical College Journal, 2019)
Kala-Azar is a devastating parasitic disease caused by Leishmania donovani, increasing in our country and turning into serious public health problem in Bangladesh due to multiple problems. The standard drug for treatment of Kala- Azar is still Sodium Stibogluconate (SAG) in our country due to high cost of liposomal Amphotericin B. The aim of this study is to see the cardiac complication and electrographic alterations during SAG therapy in standard dose. One hundred and twenty five patients (62.4% male and 37.6% female) were included in this study. All had normal ECG prior to therapy. Various electrographic alterations were noted in 31 (24.8%) of the cases after starting antimony therapy. Most common changes seen in our study were T wave inversion (24.4%), reduced amplitude of T wave (7.3%) and ventricular ectopic (8%). These changes were observed during 2nd to 3rd weeks of therapy and disappeared within two weeks of stoppage of further antimony therapy. Alteration in ECG might be the prior evidence of cardiotoxicity and might explain sudden deaths encountered during antimony in Kala-Azar. Close clinical observations and ECG monitoring of the patients receiving antimony therapy for Kala-Azar is essential for early detection of cardiotoxicity and thereby to prevent further complications including sudden death Faridpur Med. Coll. J. Jul 2018;13(2): 70-73